Acquisition of Second Language Grammar Under Incidental Learning Conditions: The Role of Frequency and Working Memory. Issue 1 (8th October 2015) - Denhovska, Nadiia; Serratrice, Ludovica; Payne, John
Abstract : Although frequency is recognized as an important factor in second language (L2) acquisition, it has remained relatively underinvestigated in terms of its impact on the acquisition of grammatical knowledge under incidental learning conditions. This article reports the results of an experiment where 100 novice adult learners were exposed to a complex noun–adjective agreement pattern in Russian under four incidental learning conditions in which type and token frequencies of the stimuli were manipulated. The results show that accuracy was greater in the low type/low token condition and that low token frequency played a more significant role than low type frequency, supporting a "starting small" approach for productive knowledge acquisition. Working memory was differentially involved in production of acquired knowledge in different conditions and not engaged when learning was facilitated by frequency.